FROM DOCTOR TO WARRIOR: A.K. GANI'S ROLE IN INDONESIA'S PHYSICAL REVOLUTION - Diko Ardhana; Dedi Irwanto (Indonesian Journal of Social Science Education (IJSSE), 2026)
This article aims to describe the role of Dr. Adnan Kapau Gani (AK Gani) in the Indonesian Physical Revolution (1945–1950) both in South Sumatra and throughout the country. As Military Governor of Southern Sumatra and Commander of SUBKOSS, he led defense strategy, guerrilla warfare, and consolidated the People's Security Army and the struggle troops. At the national level, he served as Minister of Prosperity, managed resources, formed the Planning Council, and built international cooperation through the American-Indonesian Corporation to counter the Dutch blockade. To gain recognition of Indonesian sovereignty and maintain central-regional coordination, he was also active in political diplomacy, including the Linggarjati Agreement. Using a national history approach and literature study, this research shows that AK Gani greatly helped maintain independence, create stability, and strengthen Indonesia's position in the world.